Resin film and use thereof
Patent Information
- Application Number
- CN202211250647.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2022-10-13
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-10-13
AI Technical Summary
[0005] Therefore, one object of the present invention is to provide a resin film, wherein the resin film, when measured by Fourier transform infrared spectroscopy (FTIR), has a wavelength of 2205 cm⁻¹. -1 Up to 2322cm -1 It has a spectral intensity a at 1472 cm⁻¹ -1 Up to 1523cm -1 The spectral intensity at a given location is b, and 0.70 ≤ a/b ≤ 1.95.
Smart Images

Figure BDA0003887726420000231 
Figure BDA0003887726420000241 
Figure BDA0003887726420000242
Abstract
Description
Technical Field
[0001] This invention relates to a resin film, and more particularly to a resin film having good copper foil adhesion and heat resistance, and the application of the resin film. Background Technology
[0002] Printed circuit boards (PCBs) serve as substrates for electronic devices, housing various electronic components that are electrically interconnected, providing a stable circuit operating environment. PCBs are primarily made of copper foil substrates, which are formed by alternating layers of dielectric and conductive copper foil.
[0003] In recent years, with the development of electronic devices and the progress of high performance, the size of IC packaging has gradually shrunk and become thinner. Multilayer printed circuit boards pursue high-density stacking layers, which makes the dimensional stability requirements of the substrate itself more stringent. In particular, the dielectric layer must have good copper foil adhesion and heat resistance to avoid the problem of circuit connection breakage. Summary of the Invention
[0004] The present invention aims to provide a film material with good copper foil adhesion and heat resistance. This film material can be used as a dielectric material for copper foil substrates. Compared with traditional liquid or powder materials, the film material of the present invention has the advantages of uniform thickness and is conducive to large-area application.
[0005] Therefore, one object of the present invention is to provide a resin film, wherein the resin film, when measured by Fourier transform infrared spectroscopy (FTIR), has a wavelength of 2205 cm⁻¹. -1 Up to 2322cm -1 It has a spectral intensity a at 1472 cm⁻¹ -1 Up to 1523cm -1 The spectral intensity at a given location is b, and 0.70 ≤ a / b ≤ 1.95.
[0006] In some embodiments of the present invention, the Fourier transform infrared spectroscopy measurement is obtained by measuring with a Fourier transform infrared spectrometer in the following manner: the resin film is placed in the Fourier transform infrared spectrometer, and the measurement is performed at 650 cm⁻¹. -1 Up to 4000cm -1 The absorption spectrum was measured within a certain range, and the spectral intensities a and b were determined using the attenuated total reflection method. The resolution of the Fourier transform infrared spectrometer was 1 cm⁻¹. -1 The cumulative number of spectra is 12, and the spectral intensity is the absorbance at each wavelength.
[0007] In some embodiments of the present invention, the resin film is further 2943 cm⁻¹ -1 Up to 2990cm -1 The point has a spectral intensity c, and 0.05≤c / b≤0.4.
[0008] In some embodiments of the present invention, the resin film comprises epoxy resin and cyanate ester resin.
[0009] In some embodiments of the present invention, the epoxy resin is an epoxy resin having conjugated unsaturated bonds, preferably an aromatic epoxy resin.
[0010] In some embodiments of the present invention, the epoxy resin is selected from the group consisting of: bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S type epoxy resin, phenolic epoxy resin (alkylphenolic epoxy resin), biphenyl type epoxy resin, aralkyl type epoxy resin, naphthyl ring type epoxy resin, naphthol type epoxy resin, epoxide of phenol and aromatic aldehyde condensate having phenolic hydroxyl groups, biphenyl aralkyl type epoxy resin, fluorene type epoxy resin, xanthine type epoxy resin, dicyclopentadiene type epoxy resin, triglycidyl polyisocyanate, and combinations thereof.
[0011] In some embodiments of the present invention, the cyanate resin is selected from the group consisting of: bisphenol A dicyanate, bisphenol E dicyanate resin, bisphenol F dicyanate, bisphenol S dicyanate, phenolic cyanate resin, biphenyl dicyanate, biphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)sulfide, bis(4-cyanate phenyl) ether, phenolic cyanate resin containing a dicyclopentadiene structure, and combinations thereof.
[0012] In some embodiments of the present invention, the resin film further comprises a filler, and the filler content is 70% to 88% by weight, based on the solid content of the resin film.
[0013] In some embodiments of the present invention, the filler is selected from the group consisting of: silicon dioxide, aluminum oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, talc, clay, aluminum nitride, boron nitride, aluminum hydroxide, silicon aluminum carbide, silicon carbide, sodium carbonate, titanium dioxide, zinc oxide, zirconium oxide, quartz, diamond, diamond-like material, graphite, calcined kaolin, baiji, mica, hydrotalcite, polytetrafluoroethylene (PTFE) powder, glass beads, ceramic whiskers, carbon nanotubes, strontium titanate, and combinations thereof.
[0014] In some embodiments of the present invention, the resin film further comprises carbon black.
[0015] In some embodiments of the present invention, the resin film further comprises a curing accelerator selected from the group consisting of amine curing accelerators, guanidine curing accelerators, imidazole curing accelerators, and combinations thereof.
[0016] In some embodiments of the present invention, the resin film has a thickness of 25 micrometers to 300 micrometers.
[0017] Another object of the present invention is to provide a copper foil substrate comprising a dielectric layer and a copper foil covering the surface of the dielectric layer, wherein the dielectric layer is provided by the aforementioned resin film.
[0018] Another object of the present invention is to provide an encapsulation material comprising the above-described resin film. Detailed Implementation
[0019] The following describes some specific embodiments of the present invention; however, the present invention can be practiced in many different forms and should not be construed as limited to the description herein.
[0020] Unless otherwise stated herein, the terms “a,” “the,” and similar terms used in this specification (especially in the claims) shall be understood to include both singular and plural forms.
[0021] Unless otherwise stated herein, when describing the components contained in solutions, mixtures, compositions, or resin films in this specification, they are calculated in dry weight, i.e., the weight excluding solvent. For example, when 100 parts by weight of a resin film contains 20 parts by weight of solvent and 40 parts by weight of filler, the solid content of the resin film is 80 parts by weight, and the filler content is 50 parts by weight based on the solid content of the resin film.
[0022] 1. Resin film
[0023] This invention provides a technical effect of improving the adhesion and heat resistance of resin films to metal foils (e.g., copper foils) by controlling the a / b ratio of the infrared spectrum of the resin film. The following provides a detailed description of the resin film of this invention and its applications.
[0024] 1.1. Infrared spectral properties of resin films
[0025] When the resin membrane of this invention was measured by Fourier transform infrared spectroscopy, it showed a value at 2205 cm⁻¹. -1 Up to 2322cm -1 It has a spectral intensity a at 1472 cm⁻¹ -1 Up to 1523cm -1A point has a spectral intensity b, and the ratio of spectral intensity a to spectral intensity b (a / b) is 0.70 ≤ a / b ≤ 1.95. For example, the a / b value can be 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.30, 1.31, 1.32, 1.33 1.34, 1.35, 1.36, 1.37, 1.38, 1.39, 1.40, 1.41, 1.42, 1.43, 1.44, 1.45, 1.46, 1.47, 1.48, 1.49, 1.50, 1.51, 1.52, 1.53, 1.54, 1.55, 1.56, 1.57, 1.58, 1.59, 1.60, 1.61, 1.62, 1.63, 1.64, 1.65, 1.66 The values are 1.67, 1.68, 1.69, 1.70, 1.71, 1.72, 1.73, 1.74, 1.75, 1.76, 1.77, 1.78, 1.79, 1.80, 1.81, 1.82, 1.83, 1.84, 1.85, 1.86, 1.87, 1.88, 1.89, 1.90, 1.91, 1.92, 1.93, 1.94, or 1.95, or within a range consisting of any two of the above values. In some embodiments of the present invention, the ratio (a / b) of spectral intensity a to spectral intensity b is 0.7 to 1.9. Wherein, 2205 cm⁻¹ -1 Up to 2322cm -1 The spectral intensity α at 1472 cm⁻¹ represents the absorption peak of the cyanate ester functional group, while α is the absorption peak of the cyanate ester functional group. -1 Up to 1523cm -1The spectral intensity b at that point is the absorption peak of the carbon-carbon double bond in the benzene ring. Within the specified a / b value range, a higher a / b value results in a greater proportion of triazine structures and a corresponding increase in -N lone pairs of electrons, thus increasing the adhesion of the resin film to the copper foil. Conversely, a lower a / b value results in fewer -N lone pairs of electrons and lower adhesion to the copper foil. However, when the a / b value exceeds the upper limit of the aforementioned range, the excessive triazine structure makes the resin film brittle and unable to bond effectively to the copper foil.
[0026] In some embodiments of the present invention, when the resin membrane is measured by Fourier transform infrared spectroscopy, it is at 2943 cm⁻¹. -1 Up to 2990cm -1 The location also possesses a spectral intensity c, and the ratio of spectral intensity c to spectral intensity b (a / b) is 0.05 ≤ c / b ≤ 0.4. For example, the c / b value can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, or 0.40, or fall within a range consisting of any two of the above values. Among them, 2943 cm -1 Up to 2990cm -1 The spectral intensity c at that point is the absorption of the -CH single bond within the composition, and it has a corresponding relationship with the a / b value.
[0027] The infrared spectral properties of the resin film of this invention can be obtained by measuring it using a Fourier transform infrared spectrometer as follows: the resin film is placed in the Fourier transform infrared spectrometer, and measurements are taken at 650 cm⁻¹. -1 Up to 4000cm -1 The absorption spectrum of the range was obtained, and the spectral intensities a and b were determined using the attenuated total reflectance method. The resolution of the Fourier transform infrared spectrometer was 1 cm⁻¹. -1 The cumulative number of spectra is 12, and the spectral intensity is the absorbance at each wavelength.
[0028] In this invention, spectral intensity refers to the absorbance of the resin film within a specific wavelength range, and its unit is arbitrary (au). The spectral intensity α is calculated using a 2205 cm⁻¹ wavelength range. -1 Up to 2322cm -1 The spectral intensity b is obtained by integrating the area of the line connecting the start and end points of the absorption peak within the range. The spectral intensity b is calculated at 1472 cm⁻¹.-1 Up to 1523cm -1 The range of absorption peaks is obtained by integrating the area of the line connecting the start and end points, and the spectral intensity c is calculated at 2943 cm⁻¹. -1 Up to 2990cm -1 It is obtained by integrating the area of the line connecting the starting point and the ending point of the absorption peak within the range.
[0029] The a / b and / or c / b values of the resin membrane of the present invention, measured by Fourier transform infrared spectroscopy, can be adjusted by controlling the composition of the resin membrane or the drying conditions of the resin membrane. The controllable composition of the resin membrane includes, but is not limited to, the type of resin used to prepare the resin membrane, the curing agent used, or the curing accelerator. The controllable drying conditions of the resin membrane include, but are not limited to, drying temperature and drying time. Based on the disclosure in this specification and their ordinary knowledge, those skilled in the art can select appropriate conditions to obtain the desired a / b and c / b values.
[0030] 1.2. Composition of Resin Film
[0031] 1.2.1. Epoxy resin and cyanate ester resin
[0032] Under the condition that the a / b value determined by Fourier transform infrared spectroscopy satisfies 0.70 ≤ a / b ≤ 1.95, the composition of the resin membrane of the present invention can be adjusted as needed. In some embodiments of the present invention, the resin membrane comprises epoxy resin and cyanate ester resin as resin components, or the resin component of the resin membrane is substantially composed of epoxy resin and cyanate ester resin, or the resin component of the resin membrane is composed of epoxy resin and cyanate ester resin. The resin component of the resin membrane being substantially composed of epoxy resin and cyanate ester resin means that, based on the total weight of the resin component of the resin membrane, the total content of epoxy resin and cyanate ester resin is at least 80% by weight, more specifically at least 85% by weight, for example 85% by weight, 86% by weight, 87% by weight, 88% by weight, 89% by weight, 90% by weight, 91% by weight, 92% by weight, 93% by weight, 94% by weight, 95% by weight, 96% by weight, 97% by weight, 98% by weight, or 99% by weight.
[0033] The epoxy resin may be an epoxy resin having conjugated unsaturated bonds, including aliphatic epoxy resins and aromatic epoxy resins having conjugated unsaturated bonds, and preferably aromatic epoxy resins. Examples of epoxy resins include, but are not limited to, bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S type epoxy resin, phenolic epoxy resin (alkylphenolic epoxy resin), biphenyl type epoxy resin, aralkyl type epoxy resin, naphthyl ring type epoxy resin, naphthol type epoxy resin, epoxides of phenol and aromatic aldehydes having phenolic hydroxyl groups, biphenyl aralkyl type epoxy resin, fluorene type epoxy resin, xaton type epoxy resin, dicyclopentadiene type epoxy resin, and triglycidyl polyisocyanate. The above epoxy resins may be used alone or in any combination. In some embodiments of the present invention, the resin film comprises naphthyl ring type epoxy resin and biphenyl type epoxy resin.
[0034] Commercially available epoxy resin products that can be used in the resin film of this invention include, but are not limited to, BE188 and BFE170 available from Changchun Artificial Resin Co., Ltd., NC-3000 series epoxy resins available from Nippon Kayaku Corp., and epoxy resins available from Mitsubishi Chemical Co., Ltd. YX series epoxy resins, available from DIC Corporation. HP-4032 epoxy resin, and SE80 series epoxy resins available from SHIN-AT&C.
[0035] Examples of the cyanate ester resins include, but are not limited to, bisphenol A dicyanate, bisphenol E dicyanate resin, bisphenol F dicyanate, bisphenol S dicyanate, phenolic cyanate resin, biphenyl dicyanate, biphenol dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)sulfide, bis(4-cyanate phenyl) ether, and phenolic cyanate ester resins containing a dicyclopentadiene structure. The above cyanate ester resins can be used alone or in any combination. In some embodiments of the present invention, the resin film comprises bisphenol E dicyanate resin and phenolic cyanate resin.
[0036] Commercially available cyanate resin products that can be used in the resin film of the present invention include, but are not limited to, BA-230S, PT-S60, LVT-50, PT30, and LECy, all available from LONZA Corp., wherein BA-230S and LECy are bisphenol cyanate esters, and PT-S60, LVT-50, and PT30 are phenolic cyanate esters.
[0037] Studies have found that the a-value of the resin film can be adjusted by changing the content of -OCN bonds in the cyanate ester resin, the b-value can be adjusted by changing the content of conjugated unsaturated carbon-carbon bonds in the epoxy resin, and the c-value can be adjusted by changing the methyl content in both the cyanate ester resin and the epoxy resin. Therefore, at least the a / b and c / b values of the resin film can be controlled by adjusting the above parameters.
[0038] Provided the a / b value of the resin film meets the specified range, the epoxy resin content of the resin film can be adjusted as needed. For example, based on the solid content of the resin film, the epoxy resin content can be from 2% to 25% by weight, such as 2% by weight, 3% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight, 10% by weight, 11% by weight, 12% by weight, 13% by weight, 14% by weight, 15% by weight, 16% by weight, 17% by weight, 18% by weight, 19% by weight, 20% by weight, 21% by weight, 22% by weight, 23% by weight, 24% by weight, or 25% by weight, or within a range consisting of any two of the above values. In some embodiments of the present invention, based on the solid content of the resin film, the epoxy resin content is from 5% to 18% by weight.
[0039] Provided the a / b value of the resin membrane meets the specified range, the content of cyanate resin in the resin membrane can be adjusted as needed. For example, based on the solid content of the resin membrane, the content of cyanate resin can be from 1% to 25% by weight, such as 1% by weight, 2% by weight, 3% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight, 10% by weight, 11% by weight, 12% by weight, 13% by weight, 14% by weight, 15% by weight, 16% by weight, 17% by weight, 18% by weight, 19% by weight, 20% by weight, 21% by weight, 22% by weight, 23% by weight, 24% by weight, or 25% by weight, or within a range consisting of any two of the above values. In some embodiments of the present invention, based on the solid content of the resin membrane, the content of cyanate resin can be from 1% by weight to 19% by weight.
[0040] 1.2.2. Packing
[0041] In some embodiments of the present invention, the resin membrane further comprises fillers to specifically improve the mechanical strength, thermal conductivity and dimensional stability of the resin membrane.
[0042] Examples of suitable fillers include, but are not limited to, silica (including hollow silica, spherical silica sand, etc.), alumina, magnesium oxide, magnesium hydroxide, calcium carbonate, talc, clay, aluminum nitride, boron nitride, aluminum hydroxide, silicon aluminum carbide, silicon carbide, sodium carbonate, titanium dioxide, zinc oxide, zirconium oxide, quartz, diamond, diamond-like materials, graphite, calcined kaolin, baiji clay, mica, hydrotalcite, polytetrafluoroethylene (PTFE) powder, glass beads, ceramic whiskers, carbon nanotubes, and strontium titanate. The above fillers can be used alone or in any combination.
[0043] In the thermosetting resin composition of the present invention, the shape of the filler is not particularly limited, and may be, for example, spherical, fibrous, plate-like, granular, flake-like, needle-like, etc., but the present invention is not limited thereto. In addition, the size of the filler is not particularly limited. Taking spherical or granular fillers as an example, their average particle size is generally less than 10 micrometers, preferably between 0.1 micrometers and 5 micrometers.
[0044] In addition, to increase the compatibility between the filler and other components of the resin membrane, the filler can be surface-modified with a coupling agent before being added to the resin membrane. Examples of coupling agents include, but are not limited to, silane coupling agents, titanate coupling agents, and low-polymerization-degree polysiloxane coupling agents.
[0045] The filler content can be adjusted according to the application requirements of the resin membrane. Generally speaking, based on the solid content of the resin film, the filler content can be from 50% to 90% by weight, for example, 50% by weight, 51% by weight, 52% by weight, 53% by weight, 54% by weight, 55% by weight, 56% by weight, 57% by weight, 58% by weight, 59% by weight, 60% by weight, 61% by weight, 62% by weight, 63% by weight, 64% by weight, 65% by weight, 66% by weight, 67% by weight, 68% by weight, 69% by weight, 70% by weight, 71% by weight, 72% by weight, 73% by weight, 74% by weight, 75% by weight, 76% by weight, 77% by weight, 78% by weight, 79% by weight, 80% by weight, 81% by weight, 82% by weight, 83% by weight, 84% by weight, 85% by weight, 86% by weight, 87% by weight, 88% by weight, 89% by weight, or 90% by weight, or within a range consisting of any two of the above values. In a preferred embodiment of the present invention, in order to meet the high dimensional stability requirements of multilayer printed circuit boards, the filler content is preferably 70% to 88% by weight, based on the solid content of the resin film. When the filler content is within the above range, the resin film can have excellent dimensional stability. In particular, the resin film can have excellent coefficient of thermal expansion and reduce the occurrence of warpage.
[0046] 1.2.3. Other Selected Components
[0047] The resin film of the present invention may further include other optional components as needed to adaptively improve the processability of the resin film during manufacturing or to improve the physicochemical properties of the manufactured electronic materials. Examples of optional components include, but are not limited to, solvents, curing accelerators, elastomers, flame retardants, and additives already available in the art. Examples of elastomers include, but are not limited to, polybutadiene, polyisoprene, and styrene-olefin copolymers. Examples of flame retardants include, but are not limited to, phosphorus-containing flame retardants and bromine-containing flame retardants. Examples of solvents include, but are not limited to, toluene, γ-butyrolactone, methyl ethyl ketone, cyclohexanone, butanone, acetone, xylene, methyl isobutyl ketone, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methyl-pyrolidone (NMP). Examples of curing accelerators include, but are not limited to, amine curing accelerators (DETDA-80), guanidine curing accelerators, and imidazole curing accelerators. Examples of additives existing in the art include, but are not limited to, carbon black, dispersants, toughening agents, viscosity modifiers, thixotropic agents, defoamers, leveling agents, surface treatment agents, stabilizers, and antioxidants. Each selected component can be used alone or in any combination.
[0048] In some embodiments of the present invention, the resin film further comprises a solvent, and the solvent content, based on the total weight of the resin film, may be from 3% to 16% by weight, for example, 3% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight, 10% by weight, 11% by weight, 12% by weight, 13% by weight, 14% by weight, 15% by weight, or 16% by weight, or within a range consisting of any two of the above values.
[0049] In some embodiments of the present invention, the resin film further comprises carbon black, and the carbon black content, based on the solid content of the resin film, can be from 0.1 wt% to 1 wt%, for example, 0.1 wt%, 0.15 wt%, 0.2 wt%, 0.25 wt%, 0.3 wt%, 0.35 wt%, 0.4 wt%, 0.45 wt%, 0.5 wt%, 0.55 wt%, 0.6 wt%, 0.65 wt%, 0.7 wt%, 0.75 wt%, 0.8 wt%, 0.85 wt%, 0.9 wt%, 0.95 wt%, or 1 wt%, or within a range consisting of any two of the above values. The use of carbon black enables the resin film of the present invention to appear black, which helps to effectively mask the circuit design in the fabrication of circuit encapsulation overlays.
[0050] In some embodiments of the present invention, the resin film further comprises a curing accelerator to promote the curing reaction and lower the curing temperature of the resin composition. There are no particular limitations on the content of the curing accelerator. Generally, the content of the curing accelerator, based on the solid content of the resin film, can be from 0.1 wt% to 3 wt%, for example, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2 wt%, 2.1 wt%, 2.2 wt%, 2.3 wt%, 2.4 wt%, 2.5 wt%, 2.6 wt%, 2.7 wt%, 2.8 wt%, 2.9 wt%, or 3 wt%, or within a range consisting of any two of the above values.
[0051] 1.3. Other properties of resin films
[0052] The resin film of this invention is a semi-cured film (B-stage), meaning that the resin film is dried and baked without solvent or containing only a small amount of solvent, and its resin components may have a certain degree of oligomerization but are not completely gelled. The resin film of this invention has advantages such as uniform thickness, ease of use in large-area applications, good copper foil adhesion and heat resistance, and further, in the preferred embodiment containing a high content of filler, it has excellent dimensional stability.
[0053] In some embodiments of the present invention, the thickness of the resin film can reach 25 micrometers to 300 micrometers. For example, the thickness of the resin film can be 25 micrometers, 30 micrometers, 35 micrometers, 40 micrometers, 45 micrometers, 50 micrometers, 55 micrometers, 60 micrometers, 65 micrometers, 70 micrometers, 75 micrometers, 80 micrometers, 85 micrometers, 90 micrometers, 95 micrometers, 100 micrometers, 105 micrometers, 110 micrometers, 115 micrometers, 120 micrometers, 125 micrometers, 130 micrometers, 135 micrometers, 140 micrometers, 145 micrometers, 150 micrometers, 155 micrometers, 160 micrometers, 165 micrometers. The thickness can be adjusted appropriately according to the application requirements, ranging from 170 micrometers, 175 micrometers, 180 micrometers, 185 micrometers, 190 micrometers, 195 micrometers, 200 micrometers, 205 micrometers, 210 micrometers, 215 micrometers, 220 micrometers, 225 micrometers, 230 micrometers, 235 micrometers, 240 micrometers, 245 micrometers, 250 micrometers, 255 micrometers, 260 micrometers, 265 micrometers, 270 micrometers, 275 micrometers, 280 micrometers, 285 micrometers, 290 micrometers, 295 micrometers, or 300 micrometers, or within a range of any two of the above values.
[0054] 1.4. Preparation of Resin Membrane
[0055] There are no special limitations on the preparation method of the resin film of the present invention. Those skilled in the art can prepare the resin film based on the disclosure of this specification.
[0056] For example, the resin film of the present invention can be prepared by the following method: the components used as raw materials for the resin film, including resin components, fillers, and other selected components, are uniformly mixed and dissolved or dispersed in a solvent using a stirrer to prepare a mixed liquid; the mixed liquid is uniformly coated onto a carrier film; and the film is dried at an appropriate drying temperature for an appropriate drying time to obtain a semi-cured resin film. The solvent can be any inert solvent that can dissolve or disperse the raw materials of the resin film but does not react with them, as described above, and will not be repeated here.
[0057] Studies have found that drying temperature and drying time affect the degree of reaction of the various components of the resin film, thereby affecting the a / b and c / b values of the resin film. Therefore, the a / b value of the resin film can also be adjusted by controlling the drying temperature and drying time. In some embodiments of the present invention, the drying temperature can be from 80°C to 120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, or 120°C, or within a range consisting of any two of the above values. In some embodiments of the present invention, the drying time can be from 5 minutes to 25 minutes, for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, or 25 minutes, or within a range consisting of any two of the above values.
[0058] After the resin membrane of the present invention is prepared, it can be tested within two days at room temperature to confirm its FTIR characteristics. Alternatively, if testing is not performed immediately, it can be stored at 0°C to -40°C, and when testing is required, it can be allowed to warm to room temperature and tested within two days.
[0059] For more detailed illustrative preparation steps of the resin of the present invention, please refer to the examples provided below.
[0060] 2. Application of resin films
[0061] The resin film of the present invention can be used as a dielectric layer material for printed circuit boards (PCBs). Therefore, the present invention also provides a copper foil substrate comprising a dielectric layer and a copper foil covering the surface of the dielectric layer, wherein the dielectric layer is provided by the resin film of the present invention. Specifically, the copper foil substrate of the present invention can be prepared by using a single layer of resin film or a plurality of laminated resin films as a dielectric layer, then laminating a copper foil on at least one outer surface of the dielectric layer to provide a laminate comprising the dielectric layer and the copper foil, and performing a hot-pressing operation on the laminate to obtain the copper foil substrate.
[0062] In addition, the resin film of the present invention can also be used for encapsulation. Therefore, the present invention also provides an encapsulation material comprising the above-mentioned resin film.
[0063] 3. Example
[0064] 3.1 Measurement Method
[0065] The present invention will now be further illustrated by the following specific embodiments, wherein the measuring instruments and methods used are as follows:
[0066] [Infrared Spectroscopy Measurement]
[0067] The prepared 160-micrometer-thick dried resin film was cut into 5 cm × 5 cm pieces as samples. The samples were placed in a Fourier transform infrared spectrometer, and measurements were taken at 650 cm⁻¹. -1 Up to 4000cm -1 The absorption spectrum of the range was determined, and the 2205 cm⁻¹ was measured using the attenuation total reflectance method. -1 Up to 2322cm -1 Spectral intensity at 1472 cm⁻¹ -1 Up to 1523cm -1 Spectral intensity at b, 2943 cm⁻¹ -1 Up to 2990cm -1 The spectral intensity c at the location, where the resolution of the Fourier transform infrared spectrometer is 1 cm⁻¹. -1 The spectrum was accumulated 12 times, and the spectral intensity was the absorbance at each wavelength (in arbitrary units). The calculation method was the integral area of the line connecting the start and end points of the peak within a specified range. The test instrument used the PerkinElmer Spectrum Ver10.5.3 software to calculate the integral value.
[0068] [Copper Foil Adhesion Test]
[0069] The prepared dried resin film was subjected to a temperature of 85°C to 120°C and a pressure of 5 to 10 kgf / cm². 2 The surface pressure of the copper foil is pressed onto the treated surface of a 1 ounce electrolytic copper foil (Changchun Copper Foil Grade: PLS), and then cured in an oven at 180°C for 3 hours to obtain a copper foil substrate (1).
[0070] The copper foil substrate (1) was placed in the chamber of the Pressure Cooker Test (PCT) and subjected to a temperature of 120°C and a pressure of 0.2 MPa for 48 hours to obtain the copper foil substrate (2).
[0071] The copper foil substrate (1) and copper foil substrate (2) were cut into sizes of 10 cm × 3.5 cm (MD direction × TD direction). The adhesive side of each copper foil substrate was bonded to pure glue and polypropylene board. They were pressed at 185°C with a pressure of 100 kgf / cm² for 120 seconds, then post-cured at 170°C for 1 hour. Finally, they were bonded with 3.5 mm etch-resistant tape and wet etched to obtain sample (1) and sample (2) respectively.
[0072] According to IPC-TM-650 test method 2.4.9, the tensile strength of sample (1) and sample (2) is tested respectively. If the tensile strength is greater than 0.7 kg / cm, it is recorded as “○”; if the tensile strength is between 0.5 and 0.7 kg / cm, it is recorded as “△”; if the tensile strength is less than 0.5 kg / cm, it is recorded as “╳”.
[0073] [Glass Transfer Temperature and Thermal Expansion Coefficient Test]
[0074] The prepared resin film was cured in an oven at 180°C for 3 hours to obtain a cured product. The cured product was cut into dimensions of 5 mm x 8 mm and then into 5 mm x 15 mm samples. These samples were analyzed using a Thermal Mechanical Analyzer (TMA) (TA Instruments) according to the tensile weighted method. After placing the samples in the TMA, two consecutive measurements were performed under the following conditions: stress of 50 mN, heating rate of 10°C / min, and temperature range from room temperature to 280°C. The glass transition temperature (Tg), the average linear thermal expansion coefficient (CTE1) from 50°C to 120°C, and the average linear thermal expansion coefficient (CTE2) from 180°C to 240°C were recorded. The unit of linear thermal expansion coefficient is ppm / °C. A higher glass transition temperature of the resin film indicates better heat resistance, and a lower CTE coefficient indicates better dimensional stability.
[0075] [Warpage Test]
[0076] The prepared 160-micron thick dried resin film was cut into 10 cm × 25 cm samples. The samples were placed in an oven (Zhisheng Industrial C-Sun, model: SM0-1B) and cured at 150°C for 4 hours. The warpage of the cured samples along the transverse direction (TD) was measured, calculated as the distance from the horizontal plane to the highest point of the bend at the edge of the plate. Warpage less than 2 cm was recorded as "○"; warpage between 2 and 3 cm was recorded as "△"; warpage greater than 3 cm or resin film rupture was recorded as "╳". More severe warpage (longer bend distance) or resin film rupture indicates poorer dimensional stability.
[0077] [Gelation Time Test]
[0078] Place 1 to 2 grams of resin film on a hot plate at 150°C, and measure the time GT required for the resin film to lose its fluidity while moving it with a scraper.
[0079] 3.2. Preparation of Resin Membrane
[0080] [Example 1]
[0081] Using a planetary mixer (model: ARV-310), 4.31% by weight of naphthalene ring-type epoxy resin (model: HP-4032 (purchased from DIC), 3.08 wt% biphenyl epoxy resin (model: NC-3000, purchased from Nippon Kayaku Co.), 9.67 wt% bisphenol E cyanate resin (model: Lecy, purchased from Lonza Group Co.), 4.16 wt% phenolic cyanate resin (model: PT30, purchased from Lonza Group Co.), 0.41 wt% amine curing accelerator, 0.37 wt% carbon black, and 78.00 wt% spherical silica sand filler (all based on solids content). The mixture was mixed and dispersed using a three-roller disperser, with solvent added to form a blended liquid. The solvent dosage was 9.04 parts by weight per 100 parts by weight (based on solids content).
[0082] The mixture was evenly coated onto a PET carrier film, and the wet film was scraped with a wire rod and a coating rod. Then it was dried in an oven at 100°C for 10 minutes to obtain a semi-cured resin film, and the forming result of the resin film was observed.
[0083] [Example 2]
[0084] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 5.75 wt% of naphthalene ring epoxy resin, 4.11 wt% of biphenyl epoxy resin, 7.94 wt% of bisphenol E cyanate resin, 3.42 wt% of phenolic cyanate resin, 0.41 wt% of amine curing accelerator, 0.37 wt% of carbon black, and 78.00 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 11.29 parts by weight per 100 parts by weight (based on solid content). Additionally, the drying time was adjusted to 5 minutes.
[0085] [Example 3]
[0086] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 9.52 wt% of naphthalene ring epoxy resin, 6.81 wt% of biphenyl epoxy resin, 3.42 wt% of bisphenol E cyanate resin, 1.47 wt% of phenolic cyanate resin, 0.41 wt% of amine curing accelerator, 0.37 wt% of carbon black, and 78.00 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 9.28 parts by weight per 100 parts by weight (based on solid content). Additionally, the drying time was adjusted to 5 minutes.
[0087] [Example 4]
[0088] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 7.50 wt% of naphthalene ring epoxy resin, 5.35 wt% of biphenyl epoxy resin, 10.36 wt% of bisphenol E cyanate resin, 4.46 wt% of phenolic cyanate resin, 0.46 wt% of amine curing accelerator, 0.54 wt% of carbon black, and 71.33 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 9.95 parts by weight per 100 parts by weight (based on solid content). Additionally, the drying temperature was adjusted to 120°C.
[0089] [Example 5]
[0090] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 5.87 wt% of naphthalene ring epoxy resin, 4.19 wt% of biphenyl epoxy resin, 8.11 wt% of bisphenol E cyanate resin, 3.49 wt% of phenolic cyanate resin, 0.40 wt% of amine curing accelerator, 0.54 wt% of carbon black, and 77.40 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 12.00 parts by weight per 100 parts by weight (based on solid content). Additionally, the drying temperature was adjusted to 120°C and the drying time to 5 minutes.
[0091] [Example 6]
[0092] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 3.53 wt% of naphthalene ring epoxy resin, 2.48 wt% of biphenyl epoxy resin, 4.85 wt% of bisphenol E cyanate resin, 2.09 wt% of phenolic cyanate resin, 0.20 wt% of amine curing accelerator, 0.54 wt% of carbon black, and 86.31 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 15.15 parts by weight per 100 parts by weight (based on solid content). Additionally, the drying temperature was adjusted to 120°C.
[0093] [Example 7]
[0094] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 10.21 wt% of naphthalene ring epoxy resin, 7.28 wt% of biphenyl epoxy resin, 14.10 wt% of bisphenol E cyanate resin, 6.07 wt% of phenolic cyanate resin, 0.40 wt% of amine curing accelerator, 0.54 wt% of carbon black, and 61.40 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 5.70 parts by weight per 100 parts by weight (based on solid content). In addition, the drying temperature was adjusted to 120°C and the drying time to 25 minutes.
[0095] [Example 8]
[0096] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 8.82 wt% of naphthalene ring epoxy resin, 6.30 wt% of biphenyl epoxy resin, 12.19 wt% of bisphenol E cyanate resin, 5.25 wt% of phenolic cyanate resin, 0.55 wt% of amine curing accelerator, 0.54 wt% of carbon black, and 66.35 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 9.09 parts by weight per 100 parts by weight (based on solid content). Additionally, the drying temperature was adjusted to 120°C and the drying time to 5 minutes.
[0097] [Comparative Example 1]
[0098] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 2.60 wt% of naphthalene ring epoxy resin, 1.87 wt% of biphenyl epoxy resin, 11.71 wt% of bisphenol E cyanate resin, 5.04 wt% of phenolic cyanate resin, 0.41 wt% of amine curing accelerator, 0.37 wt% of carbon black, and 78.00 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 10.44 parts by weight per 100 parts by weight (based on solid content).
[0099] [Comparative Example 2]
[0100] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 10.75 wt% of naphthalene ring epoxy resin, 7.71 wt% of biphenyl epoxy resin, 1.93 wt% of bisphenol E cyanate resin, 0.83 wt% of phenolic cyanate resin, 0.41 wt% of amine curing accelerator, 0.37 wt% of carbon black, and 78.00 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 12.73 parts by weight per 100 parts by weight (based on solid content). Additionally, the drying time was adjusted to 5 minutes.
[0101] [Comparative Example 3]
[0102] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 2.15 wt% of naphthalene ring epoxy resin, 1.53 wt% of biphenyl epoxy resin, 2.97 wt% of bisphenol E cyanate resin, 1.28 wt% of phenolic cyanate resin, 0.20 wt% of amine curing accelerator, 0.54 wt% of carbon black, and 91.33 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 17.15 parts by weight per 100 parts by weight (based on solid content). Additionally, the drying temperature was adjusted to 120°C and the drying time to 5 minutes.
[0103] [Comparative Example 4]
[0104] The resin film was prepared in the same manner as in Example 1, but the contents of each component were adjusted to 5.88 wt% of naphthalene ring epoxy resin, 4.19 wt% of biphenyl epoxy resin, 8.11 wt% of bisphenol E cyanate resin, 3.49 wt% of phenolic cyanate resin, 0.40 wt% of amine curing accelerator, 0.54 wt% of carbon black, and 77.39 wt% of spherical silica sand filler (all based on solid content), and the amount of solvent added was adjusted to 11.58 parts by weight per 100 parts by weight (based on solid content). In addition, the drying temperature was adjusted to 140°C and the drying time to 5 minutes.
[0105] The drying temperature, drying time conditions, and molding results of Examples 1 to 8 and Comparative Examples 1 to 4 are summarized in Table 1-1 below.
[0106] Table 1-1
[0107] Molding result good good good good good good Example 7 Example 8 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Molding result good good good rupture rupture Poor
[0108] As shown in Table 1-1, the resin film molding results of Examples 1 to 8 of the present invention are good. Comparative Examples 2 to 4, however, show poor molding results.
[0109] 3.3. Testing of Resin Membranes
[0110] The properties of the resin films of Examples 1 to 8 and Comparative Examples 1 to 4 were measured according to the measurement methods described above, including infrared spectral absorption intensity, copper foil adhesion, glass transition temperature, coefficient of thermal expansion, warpage, and gelation time, and the results are recorded in Tables 2-1 and 2-2 below.
[0111] Table 2-1
[0112]
[0113]
[0114] Table 2-2
[0115]
[0116] *NA indicates extremely poor flowability, making gelation testing impossible.
[0117] As shown in Tables 2-1 and 2-2, the resin films of Examples 1 to 8 of the present invention exhibit good copper foil adhesion and high glass transfer temperature, indicating good heat resistance. In contrast, Comparative Example 1 shows poor copper foil adhesion when the a / b value is higher than 1.95, and Comparative Examples 2 to 4 show poor copper foil adhesion and low glass transfer temperature when the a / b value is lower than 0.70, indicating poor heat resistance. In particular, the comparison between Example 5 and Comparative Example 4 shows that even if the raw materials of the resin film are the same, adjusting the drying conditions to make the a / b value lower than 0.70 will not achieve the effects of the present invention, indicating that the technical feature related to the a / b value is a special technical feature for achieving the effects of the present invention. In addition, the comparison between Examples 1 to 6 and Examples 7 and 8 further shows that when the a / b value satisfies 0.70≤a / b≤1.95, adjusting the filler content to a range of 70 to 88% by weight can further improve the coefficient of thermal expansion and improve the warpage of the resin film, indicating that dimensional stability can be further improved.
[0118] The above embodiments are merely illustrative of the principles and effects of the present invention and to illustrate its technical features, and are not intended to limit the scope of protection of the present invention. Any changes or arrangements that can be easily made by those skilled in the art without departing from the technical principles and spirit of the present invention are within the scope claimed by the present invention.
Claims
1. A resin film, characterized in that, When the resin membrane was measured by Fourier transform infrared spectroscopy, it was found to be at 2205 cm⁻¹. -1 Up to 2322 cm -1 It has a spectral intensity a at 1472 cm⁻¹ -1 Up to 1523 cm -1 The value at a given location has a spectral intensity b, and 0.70 ≤ a / b ≤ 1.
95. The resin film comprises epoxy resin and cyanate ester resin, wherein the epoxy resin is an epoxy resin having conjugated unsaturated bonds, and the content of the epoxy resin, based on the solid content of the resin film, is 6% to 25% by weight. The total content of the epoxy resin and the cyanate ester resin is at least 85% by weight, based on the total weight of the resin components of the resin film.
2. The resin film as described in claim 1, characterized in that, The Fourier transform infrared spectroscopy measurements were obtained using a Fourier transform infrared spectrometer as follows: the resin film was placed in the Fourier transform infrared spectrometer, and measurements were taken at 650 cm⁻¹. -1 Up to 4000 cm -1 The absorption spectrum of the range was determined, and the spectral intensities a and b were measured using the attenuation total reflectance method. The resolution of the Fourier transform infrared spectrometer was 1 cm⁻¹. -1 The cumulative number of spectra is 12, and the spectral intensity is the absorbance at each wavelength.
3. The resin film as described in claim 1, characterized in that, It is 2943 cm -1 Up to 2990 cm -1 The point has a spectral intensity c, and 0.05 ≤ c / b ≤ 0.
4.
4. The resin film as described in claim 1, characterized in that, The epoxy resin is an aromatic epoxy resin.
5. The resin film as described in claim 1, characterized in that, The epoxy resin is selected from the following group: bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S type epoxy resin, phenolic epoxy resin, biphenyl type epoxy resin, aralkyl type epoxy resin, naphthyl ring type epoxy resin, naphthol type epoxy resin, epoxide of phenol and aromatic aldehyde condensate having phenolic hydroxyl groups, biphenyl aralkyl type epoxy resin, fluorene type epoxy resin, xanthan type epoxy resin, and combinations thereof.
6. The resin film as described in claim 1, characterized in that, The cyanate resin is selected from the following group: bisphenol A dicyanate, bisphenol E dicyanate resin, bisphenol F dicyanate, bisphenol S dicyanate, phenolic cyanate resin, biphenyl dicyanate, biphenolic dicyanate, hexafluorobisphenol A dicyanate, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methyl ethylidene))benzene, bis(4-cyanate phenyl)sulfide, bis(4-cyanate phenyl) ether, phenolic cyanate resin containing a dicyclopentadiene structure, and combinations thereof.
7. The resin film as described in claim 1, characterized in that, It also contains filler, and the filler content is 70% to 88% by weight, based on the solid content of the resin film.
8. The resin film as described in claim 7, characterized in that, The filler is selected from the following group: silica, alumina, magnesium oxide, magnesium hydroxide, calcium carbonate, talc, clay, aluminum nitride, boron nitride, aluminum hydroxide, silicon aluminum carbide, silicon carbide, sodium carbonate, titanium dioxide, zinc oxide, zirconium oxide, quartz, diamond, diamond-like material, graphite, calcined kaolin, baiji, mica, hydrotalcite, polytetrafluoroethylene powder, glass beads, ceramic whiskers, carbon nanotubes, strontium titanate, and combinations thereof.
9. The resin film as described in claim 1, characterized in that, It also contains carbon black.
10. The resin film according to claim 1, characterized in that, It also includes curing accelerators selected from the following groups: amine curing accelerators, guanidine curing accelerators, imidazole curing accelerators, and combinations thereof.
11. The resin film as described in claim 1, characterized in that, The resin film has a thickness of 25 micrometers to 300 micrometers.
12. A copper foil substrate, characterized in that, It comprises a dielectric layer and a copper foil covering the surface of the dielectric layer, wherein the dielectric layer is provided by a resin film as described in any one of claims 1 to 11.
13. An encapsulation material, characterized in that, It comprises the resin film as described in any one of claims 1 to 11.
Citation Information
Patent Citations
Resin composition, prepreg, laminated board, multilayer printed wiring board and semiconductor device
CN101652425A
Dry film and printed wiring board
CN108476589A